Meridional Temperature Difference Over Pan-East Asia and its Relationship With Precipitation in Century Scales - Sheng, Bosi; Wang, Haolin; Sun, Wenbin; Li, Haiyan; Chao, Liya; Cheng, Jiayi; Qian, Gangzhen; Huang, Boyin; Li, Qingxiang (Frontiers in Environmental Science, 2021)
Based on the newly released China Merged Surface Temperature dataset (China-MST), we diagnose the leading mode of covariation between surface temperature and the summer precipitation in Eastern China (EC). A possible connection between the surface temperature in East Asia and EC summer precipitation since the last century (1901-2016) is analyzed. Results indicate that there exists a remarkable meridional dipole pattern of surface temperature, defined as the meridional temperature difference index (MTDI). Meanwhile, there is a tripolar pattern of summer precipitation, which coincides with the first principal component of summer precipitation in EC. Further analyses show that when the MTDI is high in summer, an anomalous anticyclonic/cyclonic circulation is in East Asia's mid/low latitude. The water vapor is down in the Yangtze and Huaihe River basins, and the ascending motion is weak, resulting in reduced precipitation over this region. At the same time, more water vapor and intensified ascending motion in North and South China tend to produce more summer precipitation. The opposite situations are found when the MTDI is low. Moreover, the MTDI closely relates with the Pacific Decadal Oscillation and the Atlantic Multidecadal Oscillation at interdecadal and multi-decadal scales. These results have been substantiated in the application of information flow analysis, a recently developed method in physics for the inference of causality between dynamical events.